Correlation of Lipid Ratios With the Severity of Pulmonary Alveolar Proteinosis: A Cross-Sectional Study - Yan, Xin; Gao, Yujuan; Zhao, Qi; Qiu, Xiaohua; Tian, Mi; Dai, Jinghong; Zhuang, Yi (Frontiers in Nutrition, 2021)
Background: Lipids are known to accumulate abnormally in the alveoli and circulate during pulmonary alveolar proteinosis (PAP). However, the relationship between lipid ratios and PAP is not clear. In this study, we investigated the lipid ratios in PAP patients and explored the relationships between lipid ratios and the severity of PAP. Methods:A total of 122 PAP patients were diagnosed and divided the mild- moderate PAP group (n=61) and the severe PAP group (n=61) according to the value of disease severity score (DSS). 130 healthy volunteers were classified as the control group. Routine blood examination and pulmonary function tests were performed and lipid profile were measured. Results: Compared with the control group, patients with PAP had significantly higher TG, TC/HDL-C, TG/HDL-C and non-HDL-C, while lower HDL-C (all P<0.05). Patients with the severe PAP had higher TC, TG, LDL-C, TC/HDL-C and non-HDL-C, while lower HDL-C than patients with the mild- moderate PAP (all P<0.05). Binary logistic regression analysis indicated that TC/HDL-C (OR=2.322, 95%CI 1.621-3.713, P=0.024) and non-HDL-C (OR=1.797, 95%CI 1.239-3.109, P=0.036) were all significantly correlated with the severity of PAP after adjustment for other risk factors. The AUC value of TC/HDL-C for predicting the severity of PAP was larger than that of non-HDL-C. The AUROC for TC/HDL-C was 0.741(0.654-0.828), and the optimal cut-off point for TC/HDL-C was 5.05 (sensitivity: 73.6 %, specificity: 68.1%). Conclusions: Lipid ratios, including TC-HDL-C and non-HDL-C, were independent risk factors for the severity of PAP. TC/HDL-C is a promising biomarker for the severity of PAP.